Integrating Pesantren Institutional Policies with Teaching Factory to Strengthen Entrepreneurship Education in Faith-Based Vocational Schools - Akhmad Iqbal Yuliansyah; Ernani Hadiyati; Tri Cicik Wijayanti (Journal of Educational Management Research, 2025)
This study aims to analyze strategies for strengthening entrepreneurship education through the alignment of faith-based institutional policies and the Teaching Factory (TeFa) learning model. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observations, and document analysis. Data were analyzed thematically to capture the dynamics between institutional governance, value systems, and vocational entrepreneurship learning. The findings indicate that institutional policies play a dual role as regulatory constraints and value-reinforcing mechanisms within a protective–educational framework. Key challenges identified include regulatory paradoxes, a persistent gap between theoretical learning and entrepreneurial practice, and an underdeveloped entrepreneurship ecosystem. To address these challenges, the study proposes three strategic approaches: (1) a tripartite collaboration model involving educational institutions, governing authorities, and industry partners; (2) the integration of institution-owned enterprises as a platform for implementing TeFa-based entrepreneurship learning; and (3) a multi-layered supervision system to ensure consistency with institutional values and governance. The study theoretically contributes an integrative model that bridges faith-based institutional values with industry-oriented vocational entrepreneurship education. Practically, it provides strategic insights for developing sustainable, value-based entrepreneurship ecosystems within faith-based vocational education settings.